Strategi Penanganan Pasca Panen Padi di Kecamatan Makale Kabupaten Tana Toraja Sulawesi Selatan - Sa'pang Arya; Rahman, Syamsul; Mahmud, Musdalipa (Lembaga Pengembangan Kinerja Dosen, 2025)
Along with the development of the times and increasingly competitive market demands, there is an urgent need to develop post-harvest handling strategies based on technological innovation, strengthening farmer capacity, and developing supporting infrastructure in Makale District. This strategy not only aims to reduce the level of yield loss, but also increase product added value, expand market access, and encourage agricultural-based regional economic growth. This study uses the SWOT Analysis Method used to evaluate strengths, weaknesses, opportunities and threats in the implementation of rice post-harvest handling strategies. The results of this analysis can be used to formulate recommendations for more effective and sustainable strategies for farmers and other stakeholders. The results of the study by carrying out a SWOT analysis include strengths including long experience, farmer group socialization, quality awareness, weaknesses including dominant age old, limited capital, traditional methods, high yield loss, opportunities including government programs, local rice demand, the role of extension workers, the availability of appropriate technology and Threats including extreme weather, competition with modern areas, limited infrastructure, low farmer regeneration. This study emphasizes the importance of transforming harvest-post-harvest practices from traditional to semi-modern based on farmer groups. A combination of training, provision of tools and ongoing support is essential to reduce yield losses, improve grain quality and maintain agricultural sustainability in Tana Toraja.